2004
DOI: 10.1111/j.0013-9580.2004.26003.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function in Girls with Epilepsy with Carbamazepine, Oxcarbazepine, or Valproate Monotherapy and after Withdrawal of Medication

Abstract: Summary:Purpose: Antiepileptic drugs may affect the serum thyroid hormone concentrations. The aim of this study was to evaluate thyroid function in 78 girls taking carbamazepine (CBZ), oxcarbazepine (OXC), or valproate (VPA) monotherapy for epilepsy and after withdrawal of the treatment.Methods: Forty-one girls taking VPA, 19 taking CBZ, and 18 taking OXC for epilepsy, as well as 54 healthy age-matched controls, aged 8 to 18 years, participated in the study. All the girls were examined clinically, and their pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
116
6
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(141 citation statements)
references
References 27 publications
17
116
6
2
Order By: Relevance
“…These data are in agreement with previous papers that found normal thyroid hormone levels (19,20,25,(28)(29)(30). By contrast, other studies (11,31) found normal thyroid hormone levels while TSH levels were increased. In a recent study, 36 out of 143 patients had TSHO5 m IU/l (index of subclinical hypothyroidism) during VPA treatment: 10 out of these patients also had low fT 4 levels; 9 out of these 36 patients had clinical symptoms of hypothyroidism but they are considered to have subclinical hypothyroidism because of high TSH values (32).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These data are in agreement with previous papers that found normal thyroid hormone levels (19,20,25,(28)(29)(30). By contrast, other studies (11,31) found normal thyroid hormone levels while TSH levels were increased. In a recent study, 36 out of 143 patients had TSHO5 m IU/l (index of subclinical hypothyroidism) during VPA treatment: 10 out of these patients also had low fT 4 levels; 9 out of these 36 patients had clinical symptoms of hypothyroidism but they are considered to have subclinical hypothyroidism because of high TSH values (32).…”
Section: Discussionsupporting
confidence: 93%
“…These results suggest that the changes in serum fT 4 levels are reversible. Our experience of 5 patients who have withdrawn CBZ-therapy is in agreement with previous reports (27,11).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…28,29 Valproate on the other side showed no significant change in the serum T3, T4 and TSH concentration, this results were in consistent with the other studies reported earlier in contrast other studies found normal thyroid hormone levels while TSH levels were increased. [30][31][32][33][34] This may be due to CBZ and Phenytoin induces hepatic microsomal enzymes markedly in dose-dependent fashion whereas VAL has no significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Há poucos dados disponíveis na literatura sobre potenciais interações do topiramato, gabapentina, felbamato, pregabalina e zonisamida sobre a produção, liberação e metabolismo dos hormônios tireoideanos (43). Em dois estudos clínicos, o uso de carbamazepina e oxcarbazepina associou-se à redução nos níveis de hormônios tireoideanos, que foram reversíveis com a suspensão das medicações (45,46). Há relatos em crianças de elevação do TSH (sem alterações nos níveis de T3 e T4) com uso crônico de valproato, mas esse quadro também é revertido com a supressão da droga (47,48).…”
Section: Dae E Função Tireoideanaunclassified